2005
DOI: 10.1111/j.1600-0420.2005.00490.x
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal triamcinolone acetonide in patients with macular oedema due to branch retinal vein occlusion: a pilot study

Abstract: ABSTRACT.Purpose: To evaluate treatment of macular oedema due to branch retinal vein occlusion (BRVO) with intravitreal triamcinolone acetonide. Methods: In a prospective case series, nine patients with macular oedema due to BRVO received an intravitreal injection of 4 mg triamcinolone acetonide. Examination included best-corrected visual acuity (BCVA) for distance and reading, intraocular pressure (IOP) measurement, fluorescein angiography and high resolution imaging by optical coherence tomography, preoperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
28
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 30 publications
2
28
0
Order By: Relevance
“…In a prospective nonrandomized comparative study on 11 eyes with CRVO receiving an intravitreal injection of TA, compared with 6 eyes of a control group without intravitreal injection of TA, the gain in visual acuity was significantly (p = 0.003) higher in the study group [103]. This confirms results of other reports on the beneficial effect of intravitreal TA on macular edema and visual acuity in patients with CRVO [81,82,83,84,85,86,87,88,89,90,91,92,93,94,95,96,97,98,99]. The results additionally suggest that the increase in visual acuity after IVTA injection may not last permanently in eyes with CRVO.…”
Section: Clinical Studies: Ta As Drug Treatment For Macular Edemasupporting
confidence: 81%
See 2 more Smart Citations
“…In a prospective nonrandomized comparative study on 11 eyes with CRVO receiving an intravitreal injection of TA, compared with 6 eyes of a control group without intravitreal injection of TA, the gain in visual acuity was significantly (p = 0.003) higher in the study group [103]. This confirms results of other reports on the beneficial effect of intravitreal TA on macular edema and visual acuity in patients with CRVO [81,82,83,84,85,86,87,88,89,90,91,92,93,94,95,96,97,98,99]. The results additionally suggest that the increase in visual acuity after IVTA injection may not last permanently in eyes with CRVO.…”
Section: Clinical Studies: Ta As Drug Treatment For Macular Edemasupporting
confidence: 81%
“…In an exponentially increasing number of case series studies and nonrandomized comparative studies, IVTA has been used for the treatment of BRVO [80,81,82,83,84,85,86,87,88,89,90,91,92,251]. Özkiris et al [86] evaluated the efficacy of IVTA injection on persistent macular edema in BRVO that failed to respond to previous laser photocoagulation.…”
Section: Clinical Studies: Ta As Drug Treatment For Macular Edemamentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, various medical and surgical strategies have been tried by many physicians to treat macular oedema secondary to BRVO. Several studies have demonstrated the usefulness of intravitreal injection of triamcinolone acetonide [16][17][18] and of anti-vascular endothelial growth factor (anti-VEGF) agents, such as bevacizumab 19,20 and ranibizumab, 21 in dealing with macular oedema due to BRVO. These treatment modalities have been reported to be associated with short-term promising anatomical and functional improvement in some patients with macular oedema due to BRVO.…”
Section: Introductionmentioning
confidence: 99%
“…However, there seems to be a wide variation in injection technique, and few appear to be evidence-based, as highlighted in a recently published survey. 2 The dosage for several studies looking at the use of IVTA in the treatment of macular oedema in branch retinal vein occlusions is 4 mg, [3][4][5] and in one study was 20-25 mg. 6 Ozkiris and co-workers used 8 mg to treat their patients, but the reasoning for this dose is not commented upon. The varying doses administered to patients in different studies can make it difficult to draw any definite conclusions about the appropriate therapeutic dose.…”
mentioning
confidence: 99%